MO103: ANCA Vasculitis with Renal Impairment in the Elderly. (3rd May 2022) - Chemli, Imen; Hammouda, Mouna; Ben Salem, Meriem; Ben Salah, Manel; Handous, Insaf; Letaief, Ahmed; Aloui, Sabra; Skhiri, Habib
Abstract: BACKGROUND AND AIMS: ANCA vasculitis is a serious pathology and life threatening. Kidney damage is common. Few studies have focused on ANCA vasculitis in the elderly. The geriatric population is particular by its polypathology and its polypharmacy. Our objective was to detail the clinical-biological, immunological and histological characteristics of patients aged 65 years or over with ANCA vasculitis with renal impairment as well as the therapeutic and evolutionary modalities. METHOD: This is a retrospective, monocentric and descriptive study, carried out in the nephrology department of the CHU Fattouma Bourguiba in Monastir during a period of 12 years extending between January 2008 and January 2021. We collected 21 elderly patients aged 65 years and over with ANCA vasculitis with renal impairment diagnosed in the nephrology department, according to the criteria of ACR 1990 and Chapel Hill 1994. RESULTS: The mean age of our patients was 69.52 ± 5.53 years with a predominance of women (sex ratio: 1.1). Essential hypertension was the most common medical history, observed in 19% of cases followed by diabetes and a history of asthma. The circumstance of discovery was renal signs in 80.9% of cases and haemoptysis in 9.5%. The median time between the onset of symptoms and the diagnosis was 15 days. General signs dominated the clinical picture: a deterioration in general condition was observed in 61.9% of cases, fever in 33.3% of cases and headache in 19% of cases. Proteinuria and haematuria were found in all cases, oliguria in 68.42% of cases, oedema in 36.68% and arterial hypertension in 26.31%. Extrarenal signs were dominated by respiratory involvement observed in 71.42% of cases. Microscopic polyangiitis was the most common type observed in 81% of cases, followed by granulomatosis with polyangiitis in 9.5% and eosinophilic granulomatosis with polyangiitis in 9.5%. All patients had received corticosteroid therapy with a median duration of 6 months. Intravenous cyclophosphamide was prescribed for 57% of patients. Seven patients had received corticosteroid therapy alone. In 57% of cases, maintenance treatment with azathioprine (Imurel) was administered during 17.25 ± 10.10 months. Plasmapheresis was performed only in a patient who presented with intra-alveolar haemorrhage. Complete remission was noted in four cases (19%) and partial remission in six cases (28.57%). At the third month of follow-up, 81% of patients were alive, 76.2% of cases at 1 year and 62% of cases at 5 years. Mortality was 19%. Infectious complications secondary to treatment were noted in 38.1% of cases. CONCLUSION: ANCA vasculitis in the elderly was characterized by a high clinical polymorphism. Despite the low mortality, disease-related and treatment-related morbidity was significant. Thus, an initial standardized geriatric assessment appears useful in order to better anticipate the occurrence of complications and their management.